PERLINDUNGAN HUKUM TERHADAP PEKERJA YANG IJAZAHNYA DITAHAN OLEH PERUSAHAAN - Pratiwi, Agustina Ni Made Ayu Darma (Jurnal Advokasi, 2016)
This writing was conducted due to the frequent dispute regarding labour agreement in which situated clauses that impose the labour legalized-certificate to be confiscated during the ongoing contract. This dispute occurs due to the fact that the number of job seekers are not proporsionate with the available jobs. Furthermore, the raise of the living cost cause panic situation in which the job seeker make up their mind to take the available jobs in various duty as long as they acquire a livelihood. Then, it can be deduced from this paper that the detention certificate made the company to workers in the agreement/contract of employment including the violation of human Rights. The policy applied by this company is against the other law despite the fact that there is no excisting laws regulate explicitly regarding to this matter.